Off Gas Measurements from FR Materials Exposed to a Flash Fire. Issue 2 (March 2015) - Ackerman, Mark; Batcheller, Jane; Paskaluk, Stephen
The decomposition of flame resistant (FR) materials, either through elevated temperature or contact with flames, results in a range of chemical species, some of which can be quite toxic to humans. Small scale or bench scale tests for decomposition products have been done in the past, but there were always questions as to whether these were representative of full-scale flash fire test results. To determine whether the decomposition products would be of sufficient quantity to measure and whether different FR materials would produce a "signature" set of compounds, full scale testing was undertaken. Coveralls constructed from four common FR materials were evaluated. The methodology used allowed the determination of the thermal decomposition products of FR materials when exposed to flash fire.